2017
DOI: 10.1002/anie.201708835
|View full text |Cite
|
Sign up to set email alerts
|

para‐Xylene Ultra‐selective Zeolite MFI Membranes Fabricated from Nanosheet Monolayers at the Air–Water Interface

Abstract: The control of membrane morphology and microstructure is crucial to improve the separation performance of molecular-sieve membranes. This can be enabled by making thin, dense, and uniform seed-crystal coatings, which are then intergrown into continuous membranes. Herein, we show a novel and simple floating particle coating method can give closely packed monolayers of zeolite nanosheets on nonporous or porous supports. The zeolite nanosheet monolayer is formed at the air-water interface in a conical Teflon trou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(91 citation statements)
references
References 46 publications
1
90
0
Order By: Relevance
“…[6,7] In this case,t he selectivity of Ben speculated from the sorption isotherms of EtP6b did not meet the experimental results.T he structural similarities of 2(CH)@EtP6 and 2-(Ben)@EtP6 lead to no selectivity while the differences of 2(MCH)@EtP6 and Tol@EtP6 result in MCH selectivity.This separation mechanism based on final guest-loaded crystal structures was further confirmed by Tol/Ben and Tol/CH adsorption experiments (Supporting Information,. This is quite different from robust MOFs,w here the selectivity of one gas/vapor over another can be easily recognized from sorption isotherms.…”
Section: Zuschriftenmentioning
confidence: 75%
See 3 more Smart Citations
“…[6,7] In this case,t he selectivity of Ben speculated from the sorption isotherms of EtP6b did not meet the experimental results.T he structural similarities of 2(CH)@EtP6 and 2-(Ben)@EtP6 lead to no selectivity while the differences of 2(MCH)@EtP6 and Tol@EtP6 result in MCH selectivity.This separation mechanism based on final guest-loaded crystal structures was further confirmed by Tol/Ben and Tol/CH adsorption experiments (Supporting Information,. This is quite different from robust MOFs,w here the selectivity of one gas/vapor over another can be easily recognized from sorption isotherms.…”
Section: Zuschriftenmentioning
confidence: 75%
“…[6] Thed ifficulties in finding suitable materials lie in the similar molecular sizes of cyclic aliphatics and aromatics (Scheme 1a). [6] Thed ifficulties in finding suitable materials lie in the similar molecular sizes of cyclic aliphatics and aromatics (Scheme 1a).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent works, [4,5] it has been shown that the void spaces can be effectively closed by growth of MFI domains,d riven by supply of silicate reactants from an underlying Stçber silica-derived disk support. In recent works, [4,5] it has been shown that the void spaces can be effectively closed by growth of MFI domains,d riven by supply of silicate reactants from an underlying Stçber silica-derived disk support.…”
mentioning
confidence: 99%